DNA fragmentation index and its correlation with other sperm parameters in 4833 infertile males - Patil, Priya S.; Patki, Satish M.; Patki, Shweta S.; Patki, Ujjwala S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Semen analysis forms the basic investigation for male factor of infertility. According to WHO Manual sperm values of normalcy are decreasing. Recent studies have highlighted newer parameters of sperm playing their role in the outcome of pregnancy. The aim was to study the DNA fragmentation index (DFI) and to know its correlation with other sperm parameters. Methods: A total of 4833 cases underwent routine semen analysis along with the DFI. The statistical analysis was done using SPSS using t test and ANOVA test. Results: It was observed that 52% infertile males presented late for treatment. All parameters showed a decline with advancing age. There was definite correlation between sperm count and sperm motility as well as morphology. The DFI showed significant negative correlation with sperm count. Pearson correlation showed positive correlation between DFI and sperm motility and morphology. Conclusions: The study highlights the need for increasing awareness about male factor of infertility. A thorough semen analysis along with DFI can help the clinician to explain the couple in a better way about the choice of ART and success of treatment.